Strategic leadership and its role in achieving competitiveness in industrial establishments": "A field study in Bashir Al-Siksik & Co. for the manufacture of sanitary and plastic tools (Journal of Accounting and Financial Studies ( JAFS ), 2021)
This study aims to know the role of strategic leadership to achieving competitiveness in industrial establishments by identifying the respondents’ perceptions about the level of availability of dimensions of leadership strategies (creativity and innovation, risk tolerance, available opportunities) in Bashir Al-Siksek & Partners Company for the manufacture of sanitary and plastic ware in Gaza stripTo achieve this, a questionnaire was developed and distributed to a sample of managers, auditors, accountants, and administrative employees in the study sample company. The questionnaire tool was distributed to 60 employees and employees, of which (52) were retrieved, or 86.6%, and (8) were excluded for lack of The respondents' answers were completely completed, as the questionnaires subject to statistical analysis amounted to (52) questionnaires, Several statistical methods were used in data analysis, including: descriptive statistics measures, regression analysis of variance, and multiple regression analysis. The study reached a set of results, including: The emergence of a clear interest from the industrial establishment, the study sample, in the dimensions of strategic leadership in the field of creating and investing available job opportunities in the market and seeking to exploit the circumstances surrounding the facility to achieve high profits that enhance the competitiveness of the establishment, The field of creativity and innovation in the contemporary environment requires the company to adopt contemporary concepts and methods such as (target cost, total quality, continuous improvement, value engineering) to introduce new products or develop existing products with high quality and less cost that customers can pay to achieve their satisfaction and requirements, which leads To increase sales, profits and market share compared to competitors, thus achieving the competitiveness of the facility, And the area of ​​risk tolerance that the facility works to reduce business risks to a minimum, and bears them in exchange for achieving success and making correct decisions, And the area of ​​risk tolerance that the facility works to reduce business risks to a minimum, and bears them in exchange for achieving success and making correct decisions. The study also reached a set of recommendations, including: The necessity for the establishment to pay attention to the dimensions of strategic leadership in order to enable it to maintain its level and position in the market by developing and expanding its business and its ability to outperform competitors.The necessity of the establishment’s interest in enhancing its competitiveness in order to ensure continuity and survival in the business world, providing allocations for research and development in a way that leads to cost reduction and facing risks, encouraging employees to bear the risks of economic, social, and psychological business, intensifying the knowledge effort on modern administrative issues and methods and approaches to cost management The strategy.